A lysosome‐plasma membrane‐sphingolipid axis linking lysosomal storage to cell growth arrest. Issue 10 (10th May 2018) - Samarani, Maura; Loberto, Nicoletta; Soldà, Giulia; Straniero, Letizia; Asselta, Rosanna; Duga, Stefano; Lunghi, Giulia; Zucca, Fabio A.; Mauri, Laura; Ciampa, Maria Grazia; Schiumarini, Domitilla; Bassi, Rosaria; et al.
ABSTRACT: Lysosomal accumulation of undegraded materials is a common feature of lysosomal storage diseases, neurodegenerative disorders, and the aging process. To better understand the role of lysosomal storage in the onset of cell damage, we used human fibroblasts loaded with sucrose as a model of lysosomal accumulation. Sucrose‐loaded fibroblasts displayed increased lysosomal biogenesis followed by arrested cell proliferation. Notably, we found that reduced lysosomal catabolism and autophagy impairment led to an increase in sphingolipids (i.e., sphingomyelin, glucosylceramide, ceramide, and the gangliosides GM3 and GD3), at both intracellular and plasma membrane (PM) levels. In addition, we observed an increase in the lysosomal membrane protein Lamp‐1 on the PM of sucrose‐loaded fibroblasts and a greater release of the soluble lysosomal protein cathepsin D in their extracellular medium compared with controls. These results indicate increased fusion between lysosomes and the PM, as also suggested by the increased activity of lysosomal glycosphingolipid hydrolases on the PM of sucrose‐loaded fibroblasts. The inhibition of β‐ glucocerebrosidase and nonlysosomal glucosylceramidase, both involved in ceramide production resulting from glycosphingolipid catabolism on the PM, partially restored cell proliferation. Our findings indicate the existence of a new molecular mechanism underlying cell damage triggered by lysosomal impairment.—Samarani, M., Loberto, N., Soldà, G., Straniero, L., Asselta, R., Duga, S., Lunghi, G., Zucca, F. A., Mauri, L., Ciampa, M. G., Schiumarini, D., Bassi, R., Giussani, P., Chiricozzi, E., Prinetti, A., Aureli, M., Sonnino, S. A lysosome‐plasma membrane‐sphingolipid axis linking lysosomal storage to cell growth arrest. FASEB J. 32, 5685–5702 (2018). www.fasebj.org